Diet of Pumpkinseed Sunfish (Lepomis gibbosus) and Brown Bullhead (Amerius nebulosus) in the Littoral Zone of Hamilton Harbour - Fitzgerald, Erin (My University, 1996)
Benthic macroinvertebrates, pumpkinseed sunfish (𝘓𝘦𝘱𝘰𝘮𝘪𝘴 𝘨𝘪𝘣𝘣𝘰𝘴𝘶𝘴) and brown bullhead (𝘈𝘮𝘦𝘳𝘪𝘶𝘴 𝘯𝘦𝘣𝘶𝘭𝘰𝘴𝘶𝘴) were sampled at three sites in western Hamilton Harbour and Cootes Paradise in early June 1995. The diversity, abundance, similarity and variability of the substrate benthic community and the gut contents of the fish were analyzed. The gut contents of both species of fish reflected the diversity, similarity and variability of the site at which they were caught. Mean gut fullness, analysized using prey abundance and volume, shows no significant difference between sites, suggesting that the fish were eating similar amounts of prey at all three sites. Both pumpkinseed sunfish and brown bullhead fed selectively on certain size classes and benthic taxa, including several taxonomic groups previously unreported for these species. Differences in benthic community structure at the three sites and the resultant differences in fish diet have important implications for the remediation of Hamilton Harbour. As water quality improves and the macrophyte cover increases, benthic diversity and abundance will increase. These improvements will increase the area of the littoral zone and the quality of the rearing and feeding environments for the recovering warmwater fisheries in Hamilton Harbour.
Fish Feeding in Hamilton Harbour
Keywords: sunfish; diet; harbour; bullhead